The prevalence of asthma in urban and rural Black children : an epidemiological survey - Van Niekerk, Christoffel Hendrik (Department of Paediatrics and Child Health, 2017)
This survey was undertaken: 1. to provide accurate information on the prevalence rates of asthma in Xhosa children living in an urban westernised community, Guguletu, Cape Town and in a rural traditional community, Tsolo District, Republic of Transkei; 2. to compare the findings of this survey with studies done elsewhere in the world on prevalence rates of asthma among children; and 3. to evaluate and correlate factors that may influence these rates. To acquire the above, it was necessary 1. to obtain information on the characteristics and socio-economic status of the family of each child studied; 2. to obtain information on every child relating to exposure to allergens in his immediate home environment; 3. to obtain information on the dietary pattern of every child during infancy and currently; 4. to identify the asthmatic children by subjecting every child to an appropriate exercise stimulus for detection of exercise-induced asthma judged by pulmonary function tests; 5. to conduct a clinical examination of the children. and skinfold thickness was also measured; Height, weight 6. to conduct prick skin testing to assess specific skin sensitivity to common allergens; 7. to conduct laboratory investigations relating to the allergic-immune status of the children; 8. arising out of these findings to relate the prevalence rates of asthma in the 2 samples and to suggest factors influencing the rates.